Spanish seamen (circular) - Tewson, Vincent
C01-0003-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: VICTORIA 9020 TRADES UNION CONGRESS GENERAL SECRETARY SIR WALTER CITRINE, K.B.E. TO WHOM ALL COMMUNICATIONS SHOULD BE ADDRESSED. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. Department International Our Ref. HVT/AC/332 Your Ref 8th August, 1939. SPANISH SEAMEN. With reference to my letter of 31st July, on the subject of the proposed emigration of certain of the Spanish seamen to Venezuela, we have now been informed that the purposes of the Venezuelan Government will be served if the certificate of good conduct is signed by a Justice of the Peace. If, therefore, the police authorities in your district have declined to issue such a document, will you be good enough to secure the signature of a J.P., if you are not one yourself? The formalities of the Venezuelan Government require the production of several photographs of each applicant for emigration. It should be possible to get these made at a very moderate cost, and we shall be obliged if you will meet the necessary charges; we shall of course reimburse you for any expenditure incurred in this regard. Yours sincerely, H.V. TEWSON. Assistant Secretary. 292C/946/1/3